Exploring the potential of pheophorbide A, a chlorophyll-derived compound in modulating GLUT for maintaining glucose homeostasis - Paul, Saptadipa; Pallavi, Anuma; Gandasi, Nikhil R. (Frontiers in Endocrinology, 2024)
Pheophorbide A, a chlorophyll breakdown product is primarily investigated for its anti-oxidant and anti-inflammatory activity. Recent reports on pheophorbide A have shown its potential in lowering blood glucose levels, thus leading to the exploration of its use in diabetes management. Literature has also shown its effect on enhanced insulin secretion whereas its mechanism on GSIS in pancreatic β-cells remains unexplored. Therefore, we used in silico and in vitro investigations to explore the effect of pheophorbide A on class I GLUTs. Molecular docking studies revealed better binding affinity of pheophorbide A with GLUT4 (-11.2 Kcal/mol) and GLUT1 (-10.7 Kcal/mol) when compared with metformin (-5.0 and -4.9 Kcal/mol respectively). Glucose levels are largely regulated by GLUTs where GLUT1 is one of the transporters that is ubiquitously present in human β-cells. Thus, we confirmed the stability of the complex i.e., pheophorbide A-GLUT1 using GROMACS for 100 ns. We further assessed its effect on a pancreatic β-cell line (INS-1) for its viability, using an MTT assay. Pheophorbide A (0.1 µM to 1 µM) showed a dose-dependent response on cell viability and was comparable to standard metformin. To assess how pheophorbide A mechanistically acts on GLUT1 in pancreatic β-cell, we transfected INS-1 cells with GLUT1-eGFP and checked how the treatment of pheophorbide A (0.50 µM) modulates GLUT1 trafficking using live cell imaging. We observed a significant increase in GLUT1 density when treated with pheophorbide A (0.442 ± 0.01 µm -2 ) at 20 mM glucose concentration when compared to GLUT1 control (0.234 ± 0.01 µm -2 ) and metformin (0.296 ± 0.02 µm -2 ). The average speed and distance traveled by GLUT1 puncta were observed to decrease when treated with pheophorbide A. The present study also demonstrated the capacity of pheophorbide A to enhance glucose uptake in β-cells. In conclusion, the current study's findings were validated by in silico and cellular analyses, suggesting that pheophorbide A may regulate GLUT1 and might be regarded as a potential lead for boosting the GSIS pathway thus maintaining glucose homeostasis.